Pendampingan Asuhan Keperawatan Medikal Bedah pada Pasien dengan Gangguan Sistem Persyarafan (Stroke Hemoragik) di Ruang Flamboyan RSUD Banjar - Nea Sherina; Dadan Ramdan; Nur Hidayat (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2022)
Introduction: Stroke is a rapid and sudden loss of brain function caused by impaired blood flow to the brain (ischemic) or rupture of a blood vessel in the brain (hemorrhagic). clear (pelo), changes in consciousness, visual disturbances, and others. Clinically, the symptoms that often appear in stroke patients are the presence of himiparesis or hemiplagia. Where the occurrence of damage to one side of the brain Objective: This assistance aims to provide nursing care to patients Mr. S with a medical diagnosis of Hemorrhagic Stroke in the Flamboyan Room at the Banjar City General Hospital. Method: Assistance activities are carried out by providing nursing care through 5 processes including assessment, nursing diagnosis, nursing intervention, nursing implementation, and nursing evaluation. Result: The results explain the main problems that arise with the diagnosis of ineffective cerebral tissue risk, physical mobility barriers have not been overcome because the patient died before the intervention was completed. However, the diagnosis of an ineffective breathing pattern is partially resolved because it helps in maintaining O2 in the body. Conclusion: The provision of nursing care with a medical diagnosis of Hemorrhagic Stroke was partially resolved.